Challenges in the Early Infant HIV Diagnosis and Treatment Cascade. (1st July 2020) - Mofenson, Lynne M.; Cohn, Jennifer; Sacks, Emma
Abstract : Abstract: The first step in improving morbidity and mortality among children living with HIV is the timely and early identification of HIV infection, which must be followed by rapid engagement in care and provision of antiretroviral therapy. However, in 2018, only 59% of HIV-exposed infants received an infant nucleic acid diagnostic test by age 2 months and only 54% of children living with HIV received treatment. Because infant diagnosis requires molecular techniques to detect viral nucleic acid, programs for early diagnosis of infection in infants are more complex than those in adults and often require coordination and management of multiple health facilities as well as logistic, financial, and human resource challenges. This article will discuss challenges at each step in the early infant diagnosis cascade and innovations that may help overcome these challenges.